2016
DOI: 10.1093/pcp/pcw160
|View full text |Cite
|
Sign up to set email alerts
|

NbCZF1, a Novel C2H2-Type Zinc Finger Protein, as a New Regulator of SsCut-Induced Plant Immunity inNicotiana benthamiana

Abstract: SsCut, which functions as an elicitor, can induce plant immunity. In this study, we utilized Nicotiana benthamiana and virus-induced gene silencing to decrease the expression of > 2,500 genes individually. Using this forward genetics approach, several genes were identified that, when silenced, compromised SsCut-triggered cell death based on a cell death assay. A CH-type zinc finger gene was isolated from N. benthamiana Sequence analysis indicated that the gene encodes a 27 kDa protein with 253 amino acids cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…This result suggests that chitin-induced AtRAN1mediated stomatal closure and resistance to pathogens may be related to Rboh-dependent ROS accumulation and NIA-dependent NO accumulation. Our previous work and this study indicate that elicitors with different origins can induce ROS and NO production (Zhang et al, 2010(Zhang et al, , 2014(Zhang et al, , 2016a(Zhang et al, , 2016b. Therefore, these results indicate that intracellular ROS and NO accumulation is shared among all signalling pathways in guard cells, and signalling components such as AtRAN1 mediate the intracellular accumulation of ROS and NO in guard cells.…”
Section: Studies Of Several Crop Species Including Rice Tomato Andsupporting
confidence: 61%
“…This result suggests that chitin-induced AtRAN1mediated stomatal closure and resistance to pathogens may be related to Rboh-dependent ROS accumulation and NIA-dependent NO accumulation. Our previous work and this study indicate that elicitors with different origins can induce ROS and NO production (Zhang et al, 2010(Zhang et al, , 2014(Zhang et al, , 2016a(Zhang et al, , 2016b. Therefore, these results indicate that intracellular ROS and NO accumulation is shared among all signalling pathways in guard cells, and signalling components such as AtRAN1 mediate the intracellular accumulation of ROS and NO in guard cells.…”
Section: Studies Of Several Crop Species Including Rice Tomato Andsupporting
confidence: 61%
“…Previous studies have demonstrated the role of TFs in regulating plant immunity. NbCZF1, a novel C2H2-Type zinc finger protein, is a regulator of plant defense [39] and VvDOF3 enhances powdery mildew resistance in Vitis vinifera [40]. In addition, AtMyb15 and MdMyb30 also participate in enhancing disease resistance [41,42].…”
Section: Prediction Of Cis-acting Elements and Transcription Factors mentioning
confidence: 99%
“…SsCut1 induced cell death in both dicot and monocot species and activated plant resistance against S. sclerotiorum , P. nicotianae and Phytophthora soja e ( Zhang H. et al, 2014 ). Further, SsCut1-induced cell death along with stomatal closure, ROS burst and NO production, was suppressed by silencing of a C 2 H 2 -type zinc finger gene NbCZF1 in N. benthamiana , showing that SsCut1-triggered defense could be mediated by NbCZF1-ROS-NO pathway ( Zhang et al, 2016 ). VdCUT11 induced cell death and defense responses in N. benthamiana , cotton, and tomato plants, and the enzymatic activity was required for its cell death-inducing activity ( Gui et al, 2018 ).…”
Section: Major Protein Families Of Oomycete and Fungus Apoplastic CDImentioning
confidence: 99%